Metastatic adenocarcinoma of temporal bone with collet-sicard syndrome - Subha, Sethu Thakachy; Nordin, Abdul Jalil (Mashhad University of Medical Sciences, 2018)
Introduction Metastatic tumors of the temporal bone are extremely rare. Collet-Sicard syndrome is an uncommon condition characterized by unilateral palsy of the lower four cranial nerves. The clinical features of temporal bone metastasis are nonspecific and mimic infections such as chronic otitis media and mastoiditis. Case Report This report describes a rare case of metastatic adenocarcinoma of the temporal bone causing Collet-Sicard syndrome, presenting with hearing loss, headache and ipsilateral cranial nerve palsies. The patient was a 68-year old woman initially diagnosed with extensive mastoiditis and later confirmed as having metastatic adenocarcinoma of the temporal bone, based on histopathologic findings. Conclusion Clinical presentation of metastatic carcinoma of the temporal bone can be overshadowed by infective or inflammatory conditions. This case report is to emphasize the point that a high index of clinical suspicion is necessary for the early diagnosis of this aggressive disease which carries relatively poor prognosis. This report highlights that it is crucial to suspect malignant neoplasm in patients with hearing loss, headache and cranial nerve palsies.